2007
DOI: 10.1158/0008-5472.can-07-1346
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Aldehyde Dehydrogenase 1 Family Member A1 as a Novel CD8+ T-Cell–Defined Tumor Antigen in Squamous Cell Carcinoma of the Head and Neck

Abstract: Few epitopes are available for vaccination therapy of patients with squamous cell carcinoma of the head and neck (SCCHN). Using a tumor-specific CTL, aldehyde dehydrogenase 1 family member A1 (ALDH1A1) was identified as a novel tumor antigen in SCCHN. Mass spectral analysis of peptides in tumor-derived lysates was used to determine that the CTL line recognized the HLA-A*0201 (HLA-A2) binding ALDH1A1 [88][89][90][91][92][93][94][95][96] peptide. Expression of ALDH1A1 in established SCCHN cell lines, normal muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 35 publications
6
104
0
1
Order By: Relevance
“…Its best-known functions are the retinol conversion to retinoic acid and the oxidation of toxic aldehyde metabo¬lites, such as those formed during the alcohol metabolism and certain chemotherapeutic drugs (eg, cyclophosphamide and cisplatin) (Bosron et al, 1988;Thomasson et al, 1991;Visus et al, 2007). In cancer, ALDH+ cells were identified in the breast and the brain (Ginestier et al, 2007;Rasper et al, 2010).…”
Section: Methods Of Identification Of Cancer Stem Cellsmentioning
confidence: 99%
“…Its best-known functions are the retinol conversion to retinoic acid and the oxidation of toxic aldehyde metabo¬lites, such as those formed during the alcohol metabolism and certain chemotherapeutic drugs (eg, cyclophosphamide and cisplatin) (Bosron et al, 1988;Thomasson et al, 1991;Visus et al, 2007). In cancer, ALDH+ cells were identified in the breast and the brain (Ginestier et al, 2007;Rasper et al, 2010).…”
Section: Methods Of Identification Of Cancer Stem Cellsmentioning
confidence: 99%
“…The ALDEFLUOR assay is a fluorescent reagent system, which uses the activity of the detoxifying enzyme aldehyde dehydrogenase (ALDH) to identify and isolate ALDH-expressing cells. It was originally used for the isolation of hematopoietic stem cells (Cheung et al 2007) and is now commonly used for the isolation of CSCs from many cancers, including lung, liver, bone, colon, pancreatic, prostate, head and neck, bladder, thyroid, brain, melanoma, and cervical (Visus et al 2007, Matsui et al 2008, Charafe-Jauffret et al 2010. A growing body of evidence suggests that ALDH activity is a common CSC marker.…”
Section: Thyroid Csc Biomarkersmentioning
confidence: 99%
“…Thus immuno-targeting of melanoma ALDH1A1 positive cells should not be toxic. 19 In our clinical trials, we have applied 30 000 vaccine doses so far, and we did not see any systemic adverse events related to the treatment.…”
Section: Discussionmentioning
confidence: 81%
“…19 have demonstrated that AHDL1A1 88-96 peptide is naturally presented, HLA-A2 restricted and CD8 + T cell defined antigen expressed in squamous cell carcinoma of the head and neck. Using tumor-specific CD8 + T cells, they identified ALDH1A1 as a novel tumor antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation